2017
DOI: 10.20885/eksakta.vol17.iss2.art5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Ethanolic Extract and Fraction of Salak Fruit Seeds ( Salacca Zalacca (Gaertn.) Voss. ) Using DPPH (2,2-Diphenyl-1-Picrylhydrazyl) Method

Abstract: Salak seeds have been developed as a beverage, but there was still a little amount of research that focused on salak seeds. This research was conducted to find out the chemical compounds and the antioxidant activity of ethanolic extract and fraction of salak fruits seeds ( Salacca zalacca (Gaertn.) Voss. ) which have been grown extensively in Sleman Yogyakarta. Extraction was conducted using maceration, followed by fractionation using vacuum liquid chromatography. The identification of the chemical compounds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This study's results align with the results of research conducted by others containing phenols, flavonoids, tannins, and monoterpenoids. Another study also reported that snake fruit skin extract contains flavonoids, saponins, phenols, tannins, steroids/triterpenoids, and alkaloids [11]. The phytochemical content of the ethanolic extract of Salak skin provides various benefits, such as antioxidants or skin lightening.…”
Section: Results and Discussion Phytochemical Screening And Antioxida...mentioning
confidence: 97%
“…This study's results align with the results of research conducted by others containing phenols, flavonoids, tannins, and monoterpenoids. Another study also reported that snake fruit skin extract contains flavonoids, saponins, phenols, tannins, steroids/triterpenoids, and alkaloids [11]. The phytochemical content of the ethanolic extract of Salak skin provides various benefits, such as antioxidants or skin lightening.…”
Section: Results and Discussion Phytochemical Screening And Antioxida...mentioning
confidence: 97%
“…Balinese grapes that have been dried and reduced in particle size are then extracted using 96% ethanol [11]. The extractant was filtered and then thickened using rotary vapour to produce an extract of Balinese grape [12]. BGE were then screened for their phytochemical content.…”
Section: Extract Of Bali Grapes and Phytochemical Screeningmentioning
confidence: 99%
“…However, snake peels and seeds become waste and are get ride to the land [2]. The utilization of snake fruit seeds has become necessary because the snake seeds occupy 30% of the whole snake fruit [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore this study aimed to fractionate SFS Pondoh and analyze phytochemical compounds in SFS fractions to minimize secondary metabolites in lipid fraction. The method used to separate secondary metabolites such as phenols, flavonoids, and tannins has 229.27 ± g / mL IC50 for antioxidant activity in SFS flour [3].…”
Section: Introductionmentioning
confidence: 99%